The Impact of the Dimensions of the Administrative Decision Support Systems on the Re-engineering of the Systems of the Palestinian universities in Gaza Strip from the Employees' Perspective - Mazen Jehad I. Al Shobaki (University of Science and Technology, Yemen, 2017)
This study aimed to identify the impact of the dimensions of the administrative decision support systems on the re-engineering of the systems of the Palestinian universities in Gaza Strip from the standpoint of employees. A descriptive approach was used through which a questionnaire was developed and distributed to a stratified random sample. (500) questionnaires were distributed and (449) were returned, with (89.8%) response rate. The study revealed these results: There was an effect for the potentials (physical, human, technical, and organizational design) available for the decision support systems and re-engineering of the systems in the Palestinian higher education institutions in Gaza Strip.There were significant differences between the assessment means of the study sample about the impact of decision support systems to re-engineer the systems in the Palestinian higher education institutions in Gaza Strip due to the gender variable in favor of males. There also differences due to the name of the university variable in favor of the Islamic University, Al Azhar University, Al Aqsa University, respectively. It was recommended that Palestinian higher education institutions which intend to start re-engineering the systems should be encouraged immediately start the process. These institutions should also develop the infrastructure of the decisions support systems when re-engineering their operations. Keywords: Decision support systems, Re-engineering, Palestinian higher education institutions.